Pain Management during Ultrasound Guided Transvaginal Oocyte Retrieval – A Narrative Review - Puvithra Thanikachalam; Dilip Kumar Govindan (Journal of Human Reproductive Sciences)
Transvaginal oocyte retrieval (TVOR), done for the purpose of assisted reproduction can instigate enormous pain and therefore requires adequate analgesia with the least adverse effects. As the procedure involves retrieving oocytes for in vitro fertilisation, the effect of the anaesthetic drugs on the oocyte quality should also be considered. This review focuses on the various modes of anaesthesia and the anaesthetic drugs which can be administered safely to provide effective analgesia in normal and in special conditions such as women with pre-existing comorbidities. Medline, Embase, PubMed and Cochrane electronic databases were searched according to modified Preferred Reporting Items for Systemic Reviews and Meta-Analyses guidelines. According to this review, conscious sedation appears to be the most preferred mode of anaesthesia in women undergoing TVOR owing to fewer adverse effects, faster recovery, better patient and specialist comfort and the least effect on oocyte quality and embryo development. Combining it with paracervical block resulted in lesser consumption of the anaesthetic drug, which may have a beneficial effect on the oocyte quality.